2015
DOI: 10.1007/s00265-015-1916-y
|View full text |Cite
|
Sign up to set email alerts
|

Birds receiving extra carotenoids keep singing during the sickness phase induced by inflammation

Abstract: Life history theory predicts that individuals have to trade-off resources between diverse energy-demanding activ- ities, such as mounting an immune response and performing advertisement behaviour. The availability of immunomodula- tory micronutrients can affect this trade-off. Carotenoids can upregulate both the humoral and cell-mediated immune re- sponse, but little is known about their effect on behavioural traits during the sickness phase induced by a common inflam- mation. To investigate whether dietary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…In the last decades several studies have investigated the role of the redox state in mediating the expression of visual secondary sexual traits (Alonso-Alvarez et al, 2007;McGraw, 2008;Svensson and Wong, 2011;Garratt and Brooks, 2012;Hill and Johnson, 2012;Simons et al, 2012), but until now only few of them focused on birdsong (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015Baldo et al, 2015;Costantini et al, 2015; Table 1). Studies carried out in captive male European starlings (Sturnus vulgaris) to investigate whether song activity can honestly convey information about the redox state, reported that the administration of dietary lutein through the diet was associated with an increase in song rate (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades several studies have investigated the role of the redox state in mediating the expression of visual secondary sexual traits (Alonso-Alvarez et al, 2007;McGraw, 2008;Svensson and Wong, 2011;Garratt and Brooks, 2012;Hill and Johnson, 2012;Simons et al, 2012), but until now only few of them focused on birdsong (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015Baldo et al, 2015;Costantini et al, 2015; Table 1). Studies carried out in captive male European starlings (Sturnus vulgaris) to investigate whether song activity can honestly convey information about the redox state, reported that the administration of dietary lutein through the diet was associated with an increase in song rate (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 99%
“…Studies carried out in captive male European starlings (Sturnus vulgaris) to investigate whether song activity can honestly convey information about the redox state, reported that the administration of dietary lutein through the diet was associated with an increase in song rate (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015. Lutein is a hydroxycarotenoid synthetized by autotrophic organisms as an essential photosynthetic pigment.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 99%
“…Recent studies in male European starlings found that inflammatory processes significantly decreased song rate (Casagrande et al . ) and that the antibody production caused a moderate reduction of one particular mode of singing (undirected song rate, i.e. song produced away from the nest‐box; Costantini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies show that birds undergo several hormonal and behavioural alterations when exposed to lypopolysaccharide (LPS), an endotoxin extracted from the outer membrane of Gram‐negative bacteria that elicits an immune response in the absence of a living pathogen (Bonneaud et al , Munoz et al , Casagrande et al ). In the barn swallow, for example, nestlings injected with LPS showed a reduced growth rate, an increased occurrence of fault bars in growing feathers (Romano et al ), and a lower breeding success (expressed as the ratio between paired and recruited males) in the following breeding season (Romano et al ).…”
mentioning
confidence: 99%
“…In two studies on adult pied flycatchers Ficedula hypoleuca , LPS‐injected males (Sanz et al ) and females (Ilmonen et al ) showed delayed moult onset and inhibited tail feather regrowth, respectively. Adult starlings injected with LPS reduced their song rate when exposed to a standard diet, but not when supplemented with carotenoids (Casagrande et al ).…”
mentioning
confidence: 99%